EVALUATION OF TARGET MARKET SEGMENTS FOR ENTERPRISES (Polityki Europejskie, Finanse i Marketing)
The purpose of the article is to substantiate the emergence of new – and the development of existing – factors and segmentation criteria for meeting consumer needs and increasing the efficiency of marketing activities for Ukrainian enterprises under modern market conditions. The object of the research is to analyze the process of development and any increases in the effectiveness of marketing segmentation. The subject of research is the theoretical, methodical and practical provisions of the formation of targeted marketing segmentation for the markets of Ukrainian enterprises. The goal of the research is to evaluate the direction and type of market segmentation that determines future target segments for enterprises and their share of existing markets. We present the characteristics of enterprises that work on market relations for the production and sale of computer devices that provide network connections. Our method was to estimate the direction and type of market segmentation in order to determine the prospective segments for such enterprises and their share of the existing market. In order to evaluate the attractiveness of target segments for Ukrainian enterprises, a survey was conducted to validate customer reactions. The analyzed variables included: the length of time a person uses his/her computer device; the reasons for possible changes and important settings when choosing a computer device; the timeframe for buying a computer device. The results of the questionnaire are separated by gender, social and geographic factors, as well as by family composition and age of respondents, taking into account the stages of their life cycle, as well as their educational level and professions – for three enterprises. Particular attention was paid to the psychographic factors of occupation and social class. The questionnaire also contained a self-assessment section on the psychological qualities of the consumer and on their psychography, which we analyzed. The hypotheses presented by individual factors and the consumer segment, separated by the results of the survey, and the analysis of the respondents' answers, are presented. Confirmation of the hypotheses and isolation of the consumer segment are given.